Static, transient, and fatigue design and analysis of a hip femoral stem using the finite element method - Serna-Landivar, José L. (2024)
The hip femoral stem is vital in ensuring patient support and mobility, and research into the femoral stem is critical for improving the durability and strength of orthopedic prostheses. Using the finite element method, this paper evaluates a femoral stem’s static, transient, and fatigue behaviors using three different materials: Ti-6Al-4V, CoCr alloy, and AISI 316L. ANSYS Mechanical software was used to perform the static analysis, evaluate deformations and stresses, and perform the transient analysis to simulate dynamic loading conditions. In addi-tion, a fatigue analysis was conducted to determine the resistance to repetitive load cycles. The results showed that the stresses and strains in the transient analysis were higher than in the static analysis because the transient analysis considers dynamic and time-varying loads. In addition, the Ti-6Al-4V material exhibits higher fatigue resistance, a significantly longer service life, and lower stresses in the static and transient range. These findings reaffirm the importance of selecting materials that balance stiffness, structural strength, and fatigue to optimize the performance and durability of femoral implants.